Hubungan Persepsi Masyarakat Tentang Vaksin Covid-19 dengan Keikutsertaan Imunisasi Vaksinasi Covid-19 di Wilayah Kerja Puskesmas Gantiwarno Kecamatan Pekalongan Kabupaten Lampung Timur Provinsi Lampung Tahun 2022 - Djunizar Djamaludin; Derista Hartati; Eka Trismiyana (Jurnal Ilmu Medis Indonesia, 2022)
Purpose: The purpose of this study was to examine relationship between public perception of the Covid-19 vaccine and the participation of the Covid-19 vaccine. Method: A Case control design with purposive sampling was employed and 60 participants were recruited from Ganti Warno Public Health Center in Pekalongan District, East Lampung, Lampung Province. There were 30 participants’ people who did not follow the Covid-19 vaccination and 30 people took the Covid-vaccination. A perception questionnaire was carried out and data analysis used Chi Square test. Results: Negative perception of the case group (80.0%) while the control group (13.3%) and the positive perception of the case group (20.0%) while the control group (86.7%). A significant relationship was found between public perception of the Covid-19 vaccine and the participation of the Covid-19 vaccine (p value: 0.000, OR: 26.000). Limitations: The researcher did not examine other variables such as the characteristics of the respondents, such as the last education and employment status. For further research, it is expected to examine these variables so that more complete data can be obtained. Contribution: The results of this study are expected to be useful for Public Health Center as input for improving and improving the implementation of public perceptions about the Covid-19 vaccine with the participation of the Covid-19 vaccination immunization.